Private Finance for Development : Wishful Thinking or Thinking Out of the Box? - Devine, Hilary; Peralta-Alva, Adrian; Selim, Hoda.; Sharma, Preya (Washington, D.C. : International Monetary Fund, 2021)
The Covid-19 pandemic has aggravated the tension between large development needs in infrastructure and scarce public resources. To alleviate this tension and promote a strong and job-rich recovery from the crisis, Africa needs to mobilize more financing from and to the private sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Economic Development; International Finance; International Investment; Long-Term Capital Movements